1995
DOI: 10.1366/0003702953965047
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Dissolved Gas Measurements Using Near-Infrared Raman Spectroscopy

Abstract: Near-infrared Raman spectra of several gases dissolved in an aqueous medium have been acquired and analyzed for the first time. Spectra of dissolved and gaseous CO2, SO2, N2O, dimethyl ether, and O2 are presented and compared. Raman-forbidden bands in the spectrum of gaseous dimethyl ether are observed in the dissolved spectrum; this result can be explained by relaxed selection rules due to lowered symmetry. Raman scattering enhancements in the dissolved phase are measured and shown to compare well with a theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 9 publications
3
30
2
Order By: Relevance
“…The Raman spectrum of CO 2 , in turn, is a moderately accurate monitor of its density, [22][23][24][25][26][27][28][29][30] and Raman spectroscopy can be used to determine the concentration and speciation (e.g., into CO 3 2Ϫ and HCO 3 Ϫ ) of CO 2 dissolved in water. [31][32][33] Our laboratory work 22 and that of others has shown that, as CO 2 density increases, the Raman band positions of both bands of the Fermi diad 34 downshift, whereas the spectral separation increases between these two bands. 23,25,26 We used the equation of state of Span and Wagner 35 as implemented with the program CO2Tab from ChemicaLogic Corporation 36 to calculate the density of the CO 2 in our previous laboratory experiments 22 and in the ocean experiment.…”
Section: Fig 6 Comparison Of the Raman Spectra Of Deionized Water (mentioning
confidence: 83%
See 3 more Smart Citations
“…The Raman spectrum of CO 2 , in turn, is a moderately accurate monitor of its density, [22][23][24][25][26][27][28][29][30] and Raman spectroscopy can be used to determine the concentration and speciation (e.g., into CO 3 2Ϫ and HCO 3 Ϫ ) of CO 2 dissolved in water. [31][32][33] Our laboratory work 22 and that of others has shown that, as CO 2 density increases, the Raman band positions of both bands of the Fermi diad 34 downshift, whereas the spectral separation increases between these two bands. 23,25,26 We used the equation of state of Span and Wagner 35 as implemented with the program CO2Tab from ChemicaLogic Corporation 36 to calculate the density of the CO 2 in our previous laboratory experiments 22 and in the ocean experiment.…”
Section: Fig 6 Comparison Of the Raman Spectra Of Deionized Water (mentioning
confidence: 83%
“…However, direct Raman spectroscopic -2 -observation of HCO and CO in solution is possible, although acquisition of spectra in-situ is difficult due to low 33 concentrations in natural waters. We are attempting to address this problem using the DORISS instrument.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[32][33][34] The first biological sample study was conducted on serum and whole blood samples from 69 patients over a seven-week period. 23 No sample processing or selection criteria were employed, with the exception of locating a few samples with extreme glucose concentrations to represent the range of diabetes patients' glucose levels.…”
Section: Unprocessed Samplesmentioning
confidence: 99%